REALITAS KESEHATAN DAN HAK REPRODUKSI PEREMPUAN - DARMAWATI, DARMAWATI (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2014)
Health needs including reproductive health for women is something that is vital for human life. Health factors are an integral part of the means of achieving success in life and happiness. In the context of Islam, its teachings teach the principles of health, hygiene and physical and spiritual purity. In the level, women's reproductive health, Islam give special attention. Among the teachings of Islam that justify the prohibition of reproductive health is alone among the men and women who are not mahram. This ban is a preventive measure to avoid the occurrence of adultery, so someone can keep a good woman. The implication is that a woman who avoid adultery can perform their reproductive function in a healthy and responsible.